Етично-виховна функція казки - Нікітіна, І.М. (Культура народов Причерноморья, 2004)
Странным противоречием является факт отказа родителей от сказки в процессе воспитания детей в то время, как исследования психоанализа убеждают, что разум ребенка насыщен злостью и фантазиями разрушительного характера. Такие родители очень обеспокоены состоянием агрессии у детей, игнорируя терапевтическую функцию сказки. A strange contradiction is that well-educated parents outlawed fairy tales for their children at just about the time when the findings of psychoanalysis made them aware that, far from being innocent, the mind of the young child is filled with anxious and destructive imagining (fairy stories stimulate the child’s fantasies - as do many other experiences). It is quite remarkable that these parents, so worried about not increasing their child’s anxieties, remained obvious to all the reassuring messages in fairy tales.